Therapeutic intervention and high-order adjustments of recursion - Carvalho, Cláudio (Journal of Sociocybernetics, 2016)
The introduction of second-order cybernetics on therapeutic practices required a deeper acknowledgement of the role and purpose(s) of the therapists on the transitory system they create with their patients. This requirement, forced their self-reflection as both observers and agents of change or irritation of communicative and cognitive processes. Another major consequence concerned the understanding of dysfunctions, no longer conceived as “real” independently from an epistemic standpoint that begins by delineating its composing elements and relations using a particular notation. The insertion of “second-order sciences” in therapeutic models involving psychic and communicative systems lead to a more sensible attunement of recursive interventions, due to a greater attention to high-order processes of punctuation of events and learning acquisitions. Focusing on the case of family therapy, we sustain that the acknowledgement of uncertain repercussions of interventions in the equilibrium of a system (or organization) is not a sign of weakness of therapy. Supported on Luhmann’s account of the family system, and stressing some of the affinities of his operative constructivism with second order cybernetics, we understand the uncertainties of therapy as 1) a consequence of the “individuation” of modern society and 2) a call for renewed and creative forms of therapeutic intervention. Through a brief presentation of Circular Questioning and of the resource to Reflecting Teams, we inspect how the therapeutic observation is dependent upon sequences of reentry that assume different levels of description. Acknowledging the consequences of modern forms of differentiation, Systemic therapy, but also forms of psychotherapy, underlined the frailties of pre-established modes of assessment and intervention. More profoundly, they denounced the insufficiency of normative models imposed to persons, “fixing” the coupling between the psychic and communicative forms. In a wide range of disorders, approaches that dispense with the 1) active enrolment of the patient in the changing process and 2) the recursive evaluation (and readjustment) of the punctuation of sequences, its self-reflection, tend to originate high order problems. This reopens the discussion of the unacknowledged assumptions of therapies within a new theoretical framework, concerning their first-order observers (both client/patient and therapist(s)), and the various levels whose distinctions guide their interaction